2003
DOI: 10.1029/2001tc001284
|View full text |Cite
|
Sign up to set email alerts
|

A cratonic Middle Jurassic paleopole: Callovian‐Oxfordian stillstand (J‐2 cusp), rotation of the Colorado Plateau, and Jurassic North American apparent polar wander

Abstract: Paleomagnetic results have been obtained from two sequences of the upper Middle Jurassic (upper Callovian) Summerville Formation which are located on the North American craton (north central New Mexico). The thicker of the two sections (Trujillo) exhibits a well‐defined dual‐polarity remanence, forming a magnetostratigraphy of at least 12 relatively short polarity intervals. The high reversal frequency is consistent with that recorded by the oceanic crust at this time. The second section (Romeroville) is thin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…If this is correct, then the long-term aridification of Pangea could have been caused by plate movement rather than by a change in atmospheric conditions. However, palaeomagnetic studies (May & Butler 1986;Bazard & Butler 1991;Steiner & Lucas 2000;Steiner 2003) have suggested that western Pangea remained at the same latitude until the Late Triassic. The rapid change from humid to arid conditions and the persistent humid climate in eastern tropical Pangea are arguments against this hypothesis of plate movements.…”
Section: Relationship Of the Palmarito Strata With Palaeoclimatic Facmentioning
confidence: 97%
“…If this is correct, then the long-term aridification of Pangea could have been caused by plate movement rather than by a change in atmospheric conditions. However, palaeomagnetic studies (May & Butler 1986;Bazard & Butler 1991;Steiner & Lucas 2000;Steiner 2003) have suggested that western Pangea remained at the same latitude until the Late Triassic. The rapid change from humid to arid conditions and the persistent humid climate in eastern tropical Pangea are arguments against this hypothesis of plate movements.…”
Section: Relationship Of the Palmarito Strata With Palaeoclimatic Facmentioning
confidence: 97%
“…To further complicate this analysis, the Jurassic is a time when there is rapid motion of the North American (NA) plate and a fast rate of appar-ent polar wander. The fi rst issue arises from the contrasting paleomagnetic results from northeast and southwest North America (e.g., Van Fossen and Kent, 1990;Bazard and Butler , 1991;Steiner, 2003). Middle Jurassic poles from the northeast part of the continent lie at high latitudes, near the present-day North Pole, which in turn predicts higher paleolatitudes for the NA plate.…”
Section: Discussion Of Paleomagnetic Resultsmentioning
confidence: 99%
“…The effect of the reference poles from both regions is smaller in the relative orientation of the plate with respect to the paleomeridian (and thus expected declinations and rotation estimates). The second point relates to contrasting estimates of clockwise rotation of the Colorado Plateau with respect to the craton (Molina-Garza et al, 1998;Kent and Witte, 1993;Steiner, 2003;Kent and Olsen, 2008). These estimates range from ~4° to over 15°.…”
Section: Discussion Of Paleomagnetic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) is one of the youngest. It accumulated as the supercontinent was breaking up, when the center of the plateau had reached about 20ЊN (Steiner 2003). Although some of the eolian sandstones on the plateau preserve few, if any, signs of life (e.g., the Permian White Rim Sandstone), others, including the Permian Coconino and Cedar Mesa Sandstones (McKee 1934;Loope 1984) and the Jurassic Navajo Sandstone Loope and Rowe 2003;Loope 2006), preserve abundant rhizoliths, invertebrate burrows, and vertebrate tracks.…”
Section: Introductionmentioning
confidence: 99%